Potentiality of Funori to restore physical breaks of deteriorated cellulosic fibers - Elisabetta Andrina (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In the last twenty years Funori  has become known outside Japan thanks to its capacity not to modify the appearance of the painted surface. Moreover, because of the similar chemical nature of Funori and cellulosic fibres that make the textile support, conservators have supposed Funori can restore depolymerised fibres. The experimentation  just started from this assumption and it tried to verify that supposition.